Botulinum neurotoxin injections for muscle-based (dystonia and spasticity) and non-muscle-based (neuropathic pain) pain disorders: a meta-analytic study - Siongco, Paula Ruth L; Rosales, Raymond L; Moore, Austen Peter; Freynhagen, Rainer; Arimura, Kimiyoshi; Kanovsky, Petr; Kaji, Ryuji; Fernandez, Hubert H; Dressler, Dirk (Journal of neural transmission (Vienna, Austria, 2020)
Apart from the known efficacy of Botulinum Neurotoxin Type A (BoNT/A) in hyperactive striated and smooth muscles, different pain states have become potential targets of toxin effects. This present study determined the comparative toxin effectiveness in pain reduction among those patients injected with BoNT/A in muscle-based and in non-muscle-based conditions. Randomized controlled trials (RCTs) on the effect of BoNT/A on selected pain conditions were included. The conditions were spasticity and dystonia for muscle-based pain. For non-muscle-based pain, conditions included were painful diabetic neuropathy (PDN), post-herpetic neuralgia (PHN), trigeminal neuralgia (TN), complex regional pain syndrome (CRPS), and spinal cord injury (SCI). In view of possibly differing pathophysiology, myofascial pain, temporomandibular joint (TMJ), other joint or tendon pains, cervicogenic and lumbar pains, migraine and visceral pain syndromes were excluded. Standardized mean difference was used as the effect measure and computed with STATA. 25 RCTs were analyzed. Pooled estimates showed significantly lower pain score in the Treatment group (z = 5.23, p < 0.01, 95% CI = - 0.75, - 0.34). Subgroup analyses showed that BoNT/A significantly reduced both muscle-based (z = 3.78, p < 0.01, 95% CI = - 0.72, - 0.23) and non-muscle-based (z = 3.37, p = 0.001, 95% CI = - 1.00, - 0.27) pain. Meta-regression using four covariates namely dosage, route, frequency and duration was done which revealed that dosage significantly affects standardized mean differences, while the other three covariates were insignificant. The joint F-test was found to be insignificant (p value = 0.1182). The application of the model with these covariates does not significantly explain the derived heterogeneity of standardized mean differences. In conclusion, BoNT/A can be effectively used in muscle-based and non-muscle-based pain disorders. We detected no difference between the presence and magnitude of pain relief favoring muscle-based compared to non-muscle-based pain. Thus, we cannot say whether or not there might be independent mechanisms of toxin-induced pain relief for pain generated from either muscle or nerve hyperactivity.
Keywords: Muscles; Pain; botulotoxiny typu A; dystonie; Neuromuscular Agents; Humans; BoNT/A; svaly; Dystonia; neurotoxiny; Botulinum Toxins, Type A; lidé; Neurotoxins; Botulinum neurotoxin; neuralgie; Neuralgia; Muscle-based pain; nervosvalové látky; Non-muscle-based pain